P98. CSF NFL – A new biomarker for neurodegeneration in CSVD?. Issue 8 (August 2018) - Assmann, A.; Scheumann, V.; Ludwig, A.M.; Garz, C.; Perosa, V.; Schreiber, F.; Heinze, H.J.; Görtler, M.W.; Düzel, E.; Vielhaber, S.; Schreiber, S.
Abstract : Background: Cerebrospinal fluid (CSF) neurofilament light chain (NfL) has emerged as a putative biomarker of neuroaxonal injury in various neurodegenerative diseases. Particularly, patients suffering from amyotrophic lateral sclerosis (ALS) display significantly elevated levels. We here aimed to compare CSF NfL between patients diagnosed to have cerebral small vessel disease (CSVD) and those exhibiting ALS. Supposing there to be some shared mechanisms of white matter injury we suspected to find similarly increased CSF NfL levels across the diagnostic groups. Methods: Our analysis comprised (i) n  = 22 patients with CSVD, defined according to the detectability of subcortical and cortical cerebral microbleeds and/or intracerebral hemorrhages (ICH), (ii) n  = 39 patients diagnosed to have definite, probable or probable laboratory-supported ALS according to the El Escorial criteria and (iii) n  = 31 hospital- and community-based control subjects. All cases were matched for age and sex, and all of them had CSF NfL levels available. In CSVD, cerebral MRIs were rated for the number of (i) cerebral microbleeds, (ii) enlarged perivascular spaces, (iii) lacunes and, for the existence of (a) cortical superficial siderosis and (b) white matter hyperintensities (WMH). WMH have thereby been assessed in a semiquantitative manner according to the Fazeka's visual rating scale ranging from 0 to 3 and according to the existence of different patterns (multiple subcortical spots, peri-basal ganglia WMH, anterior subcortical patches, posterior subcortical patches). ANOVA was conducted with CSF NfL as dependent variable and group as a fixed factor; for subgroup comparisons Bonferroni adjusted post hoc analysis was performed. In CSVD, bivariate correlations and Mann–Whitney U test were calculated to relate CSF NfL levels to the various MRI measures. P -values £ 0.05 were deemed to be statistically significant. Results: When considering the whole cohort CSF NfL levels were not related to age or sex. Analysis revealed a significant group effect (F(2) = 10.5, p  < 0.000), with each, CSVD patients and ALS subjects revealing significantly higher CSF NfL levels compared to controls. Interestingly, there were no group differences between CSVD and ALS, even, when considering CSVD patients without ICH ( n  = 15) or with ICH ( n  = 7) separately, deeming those diagnostic groups to display similar CSF NfL concentrations. Results remained unchanged after model adjustment for age and sex. In CSVD, there was a medium effect-size relationship between the severity of WMH according to Fazeka and CSF NfL levels ( ρ  = 0.4, p  = 0.04, one-tailed). Higher CSF NfL concentrations were, moreover, related to the existence of peri-basal ganglia WMH ( Z  = 1.9, p  = 0.06 [trend-level]). Discussion: Our data demonstrate that CSF NfL could serve as a biomarker for neuroaxonal injury in CSVD subjects, revealing similarly elevated concentrations as those found in ALS. In CSVD CSF NfL thereby seems to reflect the extent and patterns of white matter damage, as expected.